2018
DOI: 10.1016/j.cels.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting FcγR Regulation through a Multivalent Binding Model

Abstract: Many immune receptors transduce activation across the plasma membrane through their clustering. With Fcγ receptors (FcγRs), this clustering is driven by binding to antibodies of differing affinities that are in turn bound to multivalent antigen. As a consequence of this activation mechanism, accounting for and rationally manipulating immunoglobulin (Ig)G effector function is complicated by, among other factors, differing affinities between FcγR species and changes in the valency of antigen binding. In this stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 27 publications
9
40
0
Order By: Relevance
“…This led to the development of the concept of the so called A/I ratio as a prediction of the outcome of binding of IgG molecules of a given isotype based on its affinities to the inhibitory and activating receptors, respectively (13)(14)(15). Based on the A/I ratio concept mathematical models have been developed predicting IgG activity (16). However, it is to be expected that other factors such as the avidity of the immune complex which is influenced by the number of immunoglobulins bound to the antigen and the number of activating and inhibitory receptors on the surface of the respective effector cell may influence IgG effector functions (17).…”
Section: Introductionmentioning
confidence: 99%
“…This led to the development of the concept of the so called A/I ratio as a prediction of the outcome of binding of IgG molecules of a given isotype based on its affinities to the inhibitory and activating receptors, respectively (13)(14)(15). Based on the A/I ratio concept mathematical models have been developed predicting IgG activity (16). However, it is to be expected that other factors such as the avidity of the immune complex which is influenced by the number of immunoglobulins bound to the antigen and the number of activating and inhibitory receptors on the surface of the respective effector cell may influence IgG effector functions (17).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, these findings indicate that IgG-ICs are able to differentially engage an array of FcγRs and preferentially cross-link low affinity receptors FcγRIIA, IIIA, and IIB, which under serum conditions are considered the main effector FcγRs on immune cells. In addition to the different affinities of FcγRs for IgG isotypes, the IgG-IC size plays an important role in the binding to FcγRs (35,42,43). Using ICs of defined sizes, the authors demonstrated that for ICs composed of IgG2 and IgG4, larger ICs exhibit increased interaction with the low-affinity human FcγRs over smaller ICs (42).…”
Section: Overview Of Fcγrs and Igg Bindingmentioning
confidence: 99%
“…Moreover, the binding patterns were comparable to experiments using primary leukocytes that increased cytokine secretion in response to larger immune complexes. These data led to a mathematical model that describes effects of valency and IgG subclass on in vivo function (135). The differential binding due to a change in the size of immune complex can potentially lead to substantial changes in cell signaling and recent technical advances provide a means to quantitate signaling with cell-based assays (136).…”
Section: How Multivalency Impacts Igg-fcγr Interactionsmentioning
confidence: 99%